Narrow lenses for capturing the complexity of fisheries: A topic analysis of fisheries science from 1990 to 2016 - Syed, Shaheen; Borit, Melania; Spruit, Marco (Fish and fisheries (Oxford, England), 2018)
Despite increased fisheries science output and publication outlets, the global crisis in fisheries management is as present as ever. Since a narrow research focus may be a contributing factor to this failure, this study uncovers topics in fisheries research and their trends over time. This interdisciplinary research evaluates whether science is diversifying fisheries research topics in an attempt to capture the complexity of the fisheries system, or whether it is multiplying research on similar topics, attempting to achieve an in‐depth, but possibly marginal, understanding of a few selected components of this system. By utilizing latent Dirichlet allocation as a generative probabilistic topic model, we analyse a unique dataset consisting of 46,582 full‐text articles published in the last 26 years in 21 specialized scientific fisheries journals. Among the 25 topics uncovered by the model, only one (Fisheries management) refers to the human dimension of fisheries understood as socio‐ecological complex adaptive systems. The most prevalent topics in our dataset directly relating to fisheries refer to Fisheries management, Stock assessment, and Fishing gear, with Fisheries management attracting the most interest. We propose directions for future research focus that most likely could contribute to providing useful advice for successful management of fisheries.